Fundamentos para el empleo eficiente de los fertilizantes nitrogenados en la caña de azúcar en Cuba - Rodríguez Delgado, Irán (2015)
The results obtained during 45 years of research conducted in 3000 crops of field experiments under different sugarcane ecosystems of Cuba, showed that nitrogen re¬quirements are associated with the type strain, the performance that can be achieved with fertilization and soil characteristics as, hydromorphy and compaction, and the percentage of organic matter, which is effective for diagnosing the content of nitrogen in the soil indicator. With these basics a recommendation of nitrogen fertilizers in sugar cane was developed, which is an achievement and an extremely useful tool for sugarcane producer, for results that can be achieved without damaging the environment, which is perfect accordance with the principles of sustainable agriculture, that is, apply the amount of nitrogen fertilizer just needed to get optimal performance and preserve the ecosystem.